Moral ambition : mobilization and social outreach in evangelical megachurches - Elisha, Omri, 1972- (Anthropology of Christianity ;, 2011)
"In this evocative ethnography, Omri Elisha examines the hopes, frustrations, and activist strategies of American evangelical Christians as they engage socially with local communities. Focusing on two Tennessee megachurches, Moral Ambition reaches beyond political controversies over issues such as abortion, same-sex marriage, and public prayer to highlight the ways that evangelicals at the grassroots of the Christian Right promote faith-based causes intended to improve the state of social welfare. The book shows how these ministries both help churchgoers embody religious virtues and create provocative new opportunities for evangelism on a public scale. Elisha challenges conventional views of U.S. evangelicalism as narrowly individualistic, elucidating instead the inherent contradictions that activists face in their efforts to reconcile religious conservatism with a renewed interest in compassion, poverty, racial justice, and urban revivalism"--Provided by publisher.